1988
DOI: 10.1103/physrevlett.61.1752
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Negative-Ion Formation in Chemisorbed Species: The Energy and Angular Dependence of Vibrational Losses for Electron Scattering Studies of HCOO/Ni(110)

Abstract: We have studied both the energy and angular dependence of vibrational losses for the formate species chemisorbed on Ni(llO), using high-resolution electron-energy-loss spectroscopy. Temporary negativeion formation, at an incident electron energy of -14 eV, leads to a dramatic enhancement in the intensity of the symmetric O-C-O stretch. Electron emission shows a strong angular dependence which peaks at high emission angles away from the surface normal. This effect is compared to previous photoemission studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A resonance is evident in the excitation function obtained 10 degrees away from the specular direction (solid circles). Jones and Richardson (1988). (Fig.…”
Section: Detection Angle (°)mentioning
confidence: 99%
“…A resonance is evident in the excitation function obtained 10 degrees away from the specular direction (solid circles). Jones and Richardson (1988). (Fig.…”
Section: Detection Angle (°)mentioning
confidence: 99%
“…Indeed, no charging effect can be evidenced due to the limited and well-controlled thickness of the organic layer and the structural organization of such layer contributes to improve the resolution. , Moreover, due to self-organization, the extreme surface is essentially composed of the −COOH groups. This work will thus allow us to make a comparison with former studies of resonances in CO in the gas phase, in physisorbed , or chemisorbed ,, layers on different substrates, in physisorbed CO 2 , , and in adsorbed HCOOH overlayers. ,, Other works dedicated to HREELS studies of the thermal stability of alkanethiol SAMs should also be mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…This work will thus allow us to make a comparison with former studies of resonances in CO in the gas phase, 25 in physisorbed 12,29-32 or chemisorbed 28,33,34 layers on different substrates, in physisorbed CO 2 , 28,35 and in adsorbed HCOOH overlayers. 8,36,37 Other works 38 dedicated to HREELS studies of the thermal stability of alkanethiol SAMs should also be mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…Early HREELS studies of molecules chemisorbed on metal surfaces identified dipole and impact scattering as the dominant vibrational excitation processes, with the two mechanisms distinguished experimentally by changing the electron scattering geometry (specular and off-specular, respectively) . More recent studies, however, have shown that resonant vibrational excitation (eq 1) is a more common scattering process than initially thought. The incident electrons are captured in unoccupied molecular orbitals of the adsorbate (AB (ads) ), leading to the formation of a temporary negative ion ([AB (ads) ] - ). Since capture generally takes place in an orbital dominated by antibonding character, the equilibrium nuclear coordinates may differ from those of the ground-state neutral molecule.…”
Section: Introductionmentioning
confidence: 99%
“…5 More recent studies, however, have shown that resonant vibrational excitation (eq 1) is a more common scattering process than initially thought. [6][7][8][9][10][11][12][13][14][15] The incident electrons are captured in unoccupied molecular orbitals of the adsorbate (AB (ads) ), leading to the formation of a temporary negative ion ([AB (ads) ] -). Since capture generally takes place in an orbital dominated by antibonding character, the equilibrium nuclear coordinates may differ from those of the ground-state neutral molecule.…”
Section: Introductionmentioning
confidence: 99%